2012
DOI: 10.1063/1.4739316
|View full text |Cite
|
Sign up to set email alerts
|

Transition levels of defects in ZnO: Total energy and Janak's theorem methods

Abstract: Transition levels of defects are commonly calculated using either methods based on total energies of defects in relevant charge states or energy band single particle eigenvalues. The former method requires calculation of total energies of charged, perfect bulk supercells, as well as charged defect supercells, to obtain defect formation energies for various charge states. The latter method depends on Janak's theorem to obtain differences in defect formation energies for various charge states. Transition levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Several studies have been reported for ZnO using periodic hybrid density functional calculations which address the electronic structure of the bulk material and/or of the oxygen vacancy related properties. As it also holds for most of the theoretical studies on different materials, those dealing for ZnO can be broadly divided in two families: the ones using all electron methods and a linear combination of atomic orbitals with the orbitals expanded in a basis set of Gaussian type orbitals (GTO), and those describing the inner cores by means of a pseudopotential and expanding the valence electron density in a plane wave (PW) basis set . Gerosa et al presented a comparison of the two approaches for different oxides including ZnO .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported for ZnO using periodic hybrid density functional calculations which address the electronic structure of the bulk material and/or of the oxygen vacancy related properties. As it also holds for most of the theoretical studies on different materials, those dealing for ZnO can be broadly divided in two families: the ones using all electron methods and a linear combination of atomic orbitals with the orbitals expanded in a basis set of Gaussian type orbitals (GTO), and those describing the inner cores by means of a pseudopotential and expanding the valence electron density in a plane wave (PW) basis set . Gerosa et al presented a comparison of the two approaches for different oxides including ZnO .…”
Section: Introductionmentioning
confidence: 99%
“…33 The SJ transition state model is an alternative method to determine CTLs within DFT, which is successfully applied, among others, to wide gap systems. 34,35 This method does not require to compare the total energies of differently charged systems and is therefore less affected from issues arising from the supercell approach. The Kohn-Sham eigenvalues are related to the derivative of the total energy E with respect to the occupation number η i of the respective orbital, 36 …”
mentioning
confidence: 99%
“…A variety of approaches have been proposed, 22 including applications of Hubbard-U-like terms (LDA + U or GGA + U) to cation d states 40 or to multiple orbital channels, 41 the Slater-Janak transition model, 42,43 modified pseudopotentials, 44 Becke-Johnson type functionals, 45,46 combining DFT with quasiparticle calculations, 35,36 and hybrid functionals. [47][48][49][50][51][52][53][54][55][56] Hybrid functionals have emerged as the current method of choice, 22 applicable to a wide variety of systems including defects in Si, 47,48 GaAs, 51 diamond, 48 and oxides.…”
Section: Introductionmentioning
confidence: 99%